2017
DOI: 10.1111/nph.14416
|View full text |Cite
|
Sign up to set email alerts
|

Foliar uptake of radiocaesium from irrigation water by paddy rice (Oryza sativa): an overlooked pathway in contaminated environments

Abstract: Flooded (paddy) rice (Oryza sativa) can take up ions from the irrigation water by foliar uptake via the exposed stem base. We hypothesised that the stem base uptake of radiocaesium (RCs) is a pathway for rice grown in RCs-contaminated environments. We developed a bi-compartmental device which discriminates the stem base from root RCs uptake from solutions, thereby using RCs isotopes ( Cs and Cs) with< 2% solution leak between the compartments. Radiocaesium uptake was linear over time (0-24 h). Radiocaesium upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Recently, OsHAK1 has been indicated to be the main pathway to absorb cesium (Rai et al 2017). Radiocesium uptake activity by the stem base was detected in flooded rice and reducing the K + supply to the roots increased the uptake activity by the stem base (Uematsu et al 2017). Since OsHAK1 expression is induced in shoots under the K + starved condition ( Figure 1A), the foliar K + uptake activity of OsHAK1 might be important for the plants to adapt to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, OsHAK1 has been indicated to be the main pathway to absorb cesium (Rai et al 2017). Radiocesium uptake activity by the stem base was detected in flooded rice and reducing the K + supply to the roots increased the uptake activity by the stem base (Uematsu et al 2017). Since OsHAK1 expression is induced in shoots under the K + starved condition ( Figure 1A), the foliar K + uptake activity of OsHAK1 might be important for the plants to adapt to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 96%
“…The expression of OsHAK1 was induced not only in the roots but also in the shoots (Figure 1). Recent reports showed that cesium uptake by rice roots largely depends upon OsHAK1 (Rai et al 2017) and flooded rice can take up radiocesium by foliar uptake via the exposed stem base (Uematsu et al 2017). Taking those reports into consideration, we tested the K + uptake activity in shoots using leaf blades of oshak1 mutants and wild-type plants.…”
Section: Oshak1 Mediates K + Uptake From Leaf Bladesmentioning
confidence: 99%